Studi Banding Cybersex berdasarkan Gender - Febriana Mileani Garnita; Mardiawan, Oki (UNISBA Press, 2024)
Abstract. The rapid development of technology has changed most individual habits. However, this development has given rise to the phenomenon of cyber intimacy, which eventually leads to cybersex. This study aims to determine whether there are differences in cybersex behavior based on male and female genders. To identify any differences, data were analyzed using an Independent Sample T-Test involving 241 subjects who follow the @basefwbiru autobase on the social media platform X, aged 18-25 years, using Purposive Sampling. The measurement tool used in this study is The Internet Sex Screening Test (ISST) developed by Delmonico and Miller (2003) and modified by Putri (2021). The results of this study indicate that there are no differences between males and females in cybersex behavior on the @basefwbiru autobase, with the average female gender score being higher compared to males. Abstrak. Perkembangan teknologi yang pesat mengubah sebagian besar kebiasaan individu. Namun, perkembangan tersebut memunculkan fenomena keintiman siber yang pada akhirnya memunculkan cybersex. Penelitian ini bertujuan untuk mengetahui apakah terdapat perbedaan perilaku cybersex dilihat berdasarkan gender laki-laki dan perempuan. Untuk mengetahui apakah terdapat perbedaan, data dianalisis menggunakan Independent Sample T-Test yang melibatkan 241 subjek dari pengikut autobase @basefwbiru pada media sosial X yang berusia 18 – 25 tahun dengan Purposive Sampling. Alat ukur yang digunakan dalam penelitian ini adalah The Internet Sex Screening Test (ISST) yang disusun oleh Delmonico dan Miller (2003) dan dimodifikasi oleh Putri (2021). Hasil penelitian ini menunjukan bahwa tidak terdapat perbedaan antara laki-laki dan perempuan pada perilaku cybersex di Autobase @basefwbiru, dan rata-rata gender perempuan lebih tinggi dibandingkan dengan laki-laki.